2019
DOI: 10.3389/fevo.2019.00358
|View full text |Cite
|
Sign up to set email alerts
|

Climate-Driven Shifts in Soil Temperature and Moisture Regimes Suggest Opportunities to Enhance Assessments of Dryland Resilience and Resistance

Abstract: Assessing landscape patterns in climate vulnerability, as well as resilience and resistance to drought, disturbance, and invasive species, requires appropriate metrics of relevant environmental conditions. In dryland systems of western North America, soil temperature and moisture regimes have been widely utilized as an indicator of resilience to disturbance and resistance to invasive plant species by providing integrative indicators of long-term site aridity, which relates to ecosystem recovery potential and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 71 publications
(85 reference statements)
0
49
0
1
Order By: Relevance
“…Interactions among drought, disturbances and biological invasions have caused pervasive land degradation in dryland regions (Millennium Ecosystem Assessment, 2005). Estimated geographic patterns in ecological resistance and resilience are increasingly being used to guide the application of land treatments designed to prevent further impacts and rehabilitate degraded areas (Chambers et al, 2017), although current tools are often not built upon drought metrics with demonstrated importance for dryland ecosystems (Bradford et al, 2019). Quantitative estimates of ecological drought severity, like those presented here, are derived from process‐based analytical tools that can be leveraged to provide ecologically relevant foundational information about current and future drought patterns to improve these vulnerability assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions among drought, disturbances and biological invasions have caused pervasive land degradation in dryland regions (Millennium Ecosystem Assessment, 2005). Estimated geographic patterns in ecological resistance and resilience are increasingly being used to guide the application of land treatments designed to prevent further impacts and rehabilitate degraded areas (Chambers et al, 2017), although current tools are often not built upon drought metrics with demonstrated importance for dryland ecosystems (Bradford et al, 2019). Quantitative estimates of ecological drought severity, like those presented here, are derived from process‐based analytical tools that can be leveraged to provide ecologically relevant foundational information about current and future drought patterns to improve these vulnerability assessments.…”
Section: Discussionmentioning
confidence: 99%
“…These predictions were inferred to indicate apparent resilience and resistance and used to prioritize implementation of park burned-area emergency response and weed management plans (Hoh et al, 2015). More recently, the soil and ecological site attributes provided by the US Natural Resource Conservation Service (NRCS) web soil survey have been used to map current and future potential resilience and resistance across the sagebrush steppe biome (Maestas et al, 2016;Bradford et al, 2019), including in protected areas. For example, each of the separate management units of JODA are mapped almost entirely as low resilience currently and in the future (Figure 1A), a predicament also faced by other parks in the region.…”
Section: Introductionmentioning
confidence: 99%
“…To support this need, we evaluate a 7-year (2011-2017) study of native and non-native grass species' responses to a 2011 wildfire in a repeatedly burned and inherently low resilience protected-area landscape in the John Day Fossil Beds National Monument. We use a newly developed class of zero-augmented FIGURE 1 | (A) The five units of the John Day Fossil Beds National Monument, including Clarno (upper left) mapped to the current ecological resilience predictions developed by Bradford et al (2019). Note that future resilience in this region (upper left A) was predicted to remain low under climate change scenarios examined by Bradford et al (2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations